Further Research on the M/G/1 Retrial Queueing Model with Server Breakdowns - Ehmet Kasim; Geni Gupur (Journal of Applied Mathematics)
We study spectral properties of the operator which corresponds to the M/G/1 retrial queueing model with server breakdowns and obtain that all points on the imaginary axis except zero belong to the resolvent set of the operator and 0 is not an eigenvalue of the operator. Our results show that the time-dependent solution of the model is probably strongly asymptotically stable.